Zeeman effect splitting coefficients for ClO, OH and NO in some earth atmosphere applications. (July 2020) - Larsson, Richard; Lankhaar, Boy
Highlights: We present an accurate way to calculate the Zeeman effect for ClO, OH, NO. We demonstrate the effect of computing the Zeeman effect for these species for Earth applications. We make recommendations for others considering Zeeman effects in Earth's atmosphere. Abstract: We present detailed tabulated Zeeman effect splitting coefficients for ground-state ClO, OH and NO for F  ≤ 10. These species are, together with molecular oxygen, common Zeeman-affected molecules in Earth's atmosphere. The Zeeman effect is shown to be important mostly for OH. In proposed satellite observations of mesospheric OH, a circular polarization signal of close to 3 K can be expected. ClO and NO both show more than 1% circular polarization signal.